Stream Temperature Impacts Because of Changes in Air Temperature, Land Cover and Stream Discharge: Navarro River Watershed, California, USA. (3rd June 2016) - Woltemade, C. J.; Hawkins, T. W.
Abstract: Stream temperatures are critically important to aquatic ecology, especially cold‐water fish such as salmonids. Stream temperatures are influenced by multiple factors, including local climate, solar radiation on the stream channel, stream discharge volume and groundwater contributions. The Heat Source hydrodynamic and thermodynamic numerical model was used to evaluate temperatures in three stream reaches in the Navarro River watershed, California, USA. The model was calibrated and validated for summer 2015 conditions and then applied to scenarios that address changes in air temperatures, riparian forest cover and stream discharge. Modelling results indicate that stream temperatures are sensitive to changes in air temperatures and riparian forest cover and that higher discharge volume mitigates those impacts. Modelled stream maximum weekly average temperatures (MWAT) increased by 1.5–2.3°C in response to an air temperature increases of 3.5°C under low flow conditions (drought) but by only 0.9–2.0°C under moderate flow. Complete removal of riparian forest in a large‐scale forest fire would increase MWAT by 2.2–5.9°C in low discharges and by 1.0–4.4°C under moderate discharge. Riparian zone reforestation would decrease MWATs by less than 0.8°C, a modest change reflecting high existing shade on the modelled stream reaches. Comparison of identical climate and land cover change scenarios under low and moderate discharge conditions reveals that efforts to conserve stream discharge volume could be an effective mechanism to mitigate stream temperature increases. Copyright © 2016 John Wiley & Sons, Ltd.